Bohater o wielu twarzach. Ewolucja syjonistycznego mitu Sabry we współczesnym izraelskim kinie wojennym - PIETRZAK, MACIEJ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
The concept of the New Jew was one of the most important founding myths of Zionism. During the construction of a Jewish state in Palestine, the New Jew was hailed Sabra (with reference to the kind of prickly pear popular in this region). In the twentieth century, the figure of Sabra became an important element of the identity and culture of Israelis. The main purpose of this article is to show the evolution of the mythical narrative typical for the cinematic incarnations of Sabra, which in recent decades has taken place in Israeli war films.